Od Mehike do Brazilije, od starodavne Kitajske do novega konfucianizma - Pihler Ciglič, Barbara (Ars et humanitas, 2016)
The paper presents a general framework of the beginnings and development of sinological studies in geographically, politically and culturally very diverse Latin America, and highlights current issues and trends therein. In the 21st century the fastgrowing relationship between China and Latin America is refl ected in the accelerated creation of diverse economic-political, academic and educational institutions, publications and in the organization of numerous international conferences and scientifi c symposia. Th e study analyses the development of Confucian Studies - fi rst, through reviewing the most important translations and publications of the 20th century in connection with "the intellectual movement" in Latin America, and, second, through an illustrative commentary on the most renowned scientifi c articles and monographs. Th e study initially focuses on Mexico, the country with the longest sinological tradition in Latin America, where the Centro de Estudios de Asia y África at El Colegio de México is still regarded to be one of the most prominent Latin American centres for Asian and African Studies. Th e focus then shift s to Brazil, which seems, of all the countries in Latin America, to have the least well-established tradition in Chinese studies and Confucianism. The central premise of sinological and Confucian studies in these two countries is presented through the prism of major studies of two modern sinologists, Chen Yong (El Colegio de México) and André Bueno (Universidade do Estado de Rio de Janeiro).
Keywords: Bueno, André; El Colegio de México; konfucianizem; Latinska Amerika; sinologija; Yong, Chen